Imunopatogenesis Penyakit Paru Obstruktif Kronik : [Immunopathogenesis Update of COPD] - Resti Yudhawati; Yuyus Dwi Prasetiyo (Jurnal Respirasi, 2018)
Chronic Obstructive Pulmonary Disease (COPD) is an inflammatory airway disease and complicated lung tissue. The airways of patients with COPD contain many inflammatory cells including neutrophils, macrophages, CD8 T lymphocytes, CD4 T lymphocytes and dendritic cells, each of which has its own role and interacts with COPD immunopathogenesis. The inflammatory response in people with COPD involves innate immunity (neutrophils, macrophages, eosinophils, mast cells, natural killer cells, and dendritic cells) and adaptive immunity (T and B lymphocytes), but there is also activation of structual cells such as alveolar epithelial cells endothelial cells and fibroblasts. Inflammation of the respiratory tract in COPD will persist even after quitting smoking, this can be caused by damage to the extracellular matrix will release proinflammatory cytokines which are neutrophil and monocyte chemotaxis, impaired alveolar macrophages which result in impaired cleaning of apoptotic cells and pathogenic microbes and oxidative stress will cause DNA double chain damage.